Organometallic Ruthenium Nitrosyl Obtained by C–H Bond Activation – Photoinduced Delivery of Nitric Oxide and NO‐Mediated Antiproliferation Activity Studies. Issue 45 (28th November 2017) - Kumar, Rajan; Yadav, Anjlika; Ratnam, Anand; Kumar, Sushil; Bala, Manju; Sur, Debpali; Narang, Shikha; Singh, Udai P.; Mandal, Prabhat K.; Ghosh, Kaushik
Abstract : The azo dye methyl red, which has carboxylato and azo functional groups, was used as a ligand for the synthesis of the cyclometalated Ru III complex [Ru(L 1 )(PPh3 )2 Cl] (1, L 1 H2 = 2‐{[4‐(dimethylamino)phenyl]diazenyl}benzoic acid) through C–H bond activation. Complex1 was treated with nitric oxide to afford the organometallic ruthenium nitrosyl complex [Ru(L 2 H)(PPh3 )2 (NO)Cl][ClO4 ] (1a, L 2 H = 2‐{[4‐(dimethylamino)‐3‐nitrophenyl]diazenyl}benzoic acid). The molecular structures of1· CH3 OH and1a· CH3 OH were determined by X‐ray crystallography. The diamagnetic complex1a with S = 0 ground state was studied by 1 H and 31 P NMR spectroscopy. In the nitrosyl complex, the coordinated NO is photolabile under UV and visible light, and the liberated NO was trapped by reduced myoglobin. The NO, photoreleased under visible light, was utilized in antiproliferation activity studies on human (A549, HEK293T, and HeLa) and mouse (NIH3T3) cancer cell lines. Abstract : The cyclometalated Ru III complex [Ru(L 1 )(PPh3 )2 Cl] (1, H2 L 1 = methyl red) and the ruthenium nitrosyl complex [Ru(L 2 H)(PPh3 )2 (NO)Cl][ClO4 ] (1a ) are synthesized and characterized through spectroscopic studies. The molecular structures of1· CH3 OH and1a· CH3 OH are determined by X‐ray crystallography. The coordinated NO in1a is photolabile under visible light, and the photoreleased NO is cytotoxic.